The Influence of Charismatic Church Development on Religious Christians Life in the City of Semarang 1970-2015 - Oni Andhi Asmara; Endang Susilowati; Agustinus Supriyono (Indonesian Historical Studies, 2020)
This article discusses the development of the Charismatic church on the Christians life in Semarang City in 1970-2015 using historical methods and using social religion approach. Since its inception in 1970, the Charismatic church in the city of Semarang has had a major influence on the Christian life in the city. A series of innovations in worship and evangelism that are adapted to the times have made the Charismatic church much in demand by Christians in big cities, one of them is Semarang. Christian interest in the Charismatic church can be seen from the development of the number of Charismatic churches in the city of Semarang. One of the Charismatic churches that is experiencing rapid development is JKI Injil Kerajaan. In the beginning, there were 25 people in the congregations. One decade later it reached 3,557 people and continued to increase to 13,324 people on the next decade. This rapid development has brought significant changes to the Christians life in the city of Semarang. It can be seen, among others, from the increasing number of churches that are full of Charismatic churches at worship services. But on the other hand, the presence of Charismatic church with a new pattern of worship caused less harmonious relationship between non-Charismatic churches and charismatic churches as the result of the high increasing number of original church people who moved to the Charismatic church. It is because Christians in Semarang are mostly more interested in taking worship in the Charismatic church.